Integracja danych z różnych źródeł dla potrzeb spisu wirtualnego - NSP 2011 - Gołata, Elżbieta (Integrating Data from Different Sources for Virtual Census 2011, 2009)
The paper presents the idea of integrating different data sources to meet the needs of population census 2011, which is planned in Poland as the 'virtual' census making use of administration registers. It discusses the redesign of production process of social statistics that comes from the underlying tendency to increase efficiency by exhaustive use of all the available data sources. The author presents the international census recommendations in the field of economic activity in view of core topics and non-core topics and their prospective availability in administration records. Methods of data integration are presented together with the proposition of their implementation in the census process illustrated by economic activity data from the previous census 2002 and Labour Force Survey. Advantages and disadvantages of the register based population census are summarized. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 88-96